Subclinical course of adult visceral Niemann-Pick type C1 disease. A rare or underdiagnosed disorder? - Dvorakova, L; Sikora, J; Hrebicek, M; Hulkova, H; Bouckova, M; Stolnaja, L; Elleder, M (Journal of inherited metabolic disease, 2006)
We present the third case of Niemann-Pick disease type C without neurological symptoms. The patient was a 53-year-old woman without significant prior health problems who died of acute pulmonary embolism. Autopsy findings of hepatosplenomegaly, lymphadenopathy and ceroid-rich foam cells raised the suspicion of the visceral form of acid sphingomyelinase deficiency (Niemann-Pick disease type B; NPB) or a much rarer disorder, variant adult visceral form of Niemann-Pick disease type C (NPC). To verify the histopathological findings, SMPD1, NPC1 and NPC2 genes were analysed. Two novel sequence variants, c.1997G>A (S666N) and c.2882A>G (N961S) were detected in the NPC1 gene. No pathogenic sequence variants were found either in the SMPD1 gene mutated in NPB or in NPC2 gene. The pathogenicity of both NPC1 variants was supported by their location in regions important for the protein function. Both variations were not found in more than 300 control alleles. Identified sequence variations confirm the diagnosis of the extremely rare adult visceral form of Niemann-Pick disease type C, which is otherwise dominated by neurovisceral symptoms. Although only three patients have been reported, this (most probably underdiagnosed) form of NPC should be considered in differential diagnosis of isolated hepatosplenomegaly with foam cells in adulthood.
Keywords: glykoproteiny; intracelulární signální peptidy a proteiny; mutace; Sphingomyelin Phosphodiesterase; slezina; Brain; sfingomyelinfosfodiesterasa; Niemannova-Pickova nemoc typu C; membránové glykoproteiny; molekulární sekvence - údaje; Amino Acid Sequence; Intracellular Signaling Peptides and Proteins; Sequence Alignment; Niemann-Pick Disease, Type C; sekvenční seřazení; Vesicular Transport Proteins; Niemann-Pick C1 Protein; Glycoproteins; Spleen; Carrier Proteins; Animals; lidé; ženské pohlaví; játra; Humans; zvířata; protein NPC1; Membrane Glycoproteins; vezikulární transportní proteiny; mozek; sekvence aminokyselin; polymorfismus délky restrikčních fragmentů; Molecular Sequence Data; Mutation; Liver; Female; lidé středního věku; transportní proteiny; Polymorphism, Restriction Fragment Length; Middle Aged